2016
DOI: 10.1080/23273798.2016.1179770
|View full text |Cite
|
Sign up to set email alerts
|

Masked constituent priming of English compounds in native and non-native speakers

Abstract: The present research explores the degree of morphological structure of compound words in the native and nonnative lexicons, and provides additional data on the access to these representations. Native and nonnative speakers (L1 Spanish) of English were tested using a lexical decision task with masked priming of the compound's constituents in isolation, including two orthographic conditions to control for a potential orthographic locus of effects. Both groups displayed reliable priming effects, unmediated by sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 68 publications
0
15
1
Order By: Relevance
“…Masked priming studies, for example, revealed efficient priming effects for both the head and the modifier components of compounds, and for both transparent and opaque compounds Duñabeitia, Laka, Perea, & Carreiras, 2009;Fiorentino & Fund-Reznicek, 2009). Furthermore, studies comparing L1 and proficient L2 speakers found similar effects of decomposition of compounds for both speaker groups (González Alonso, Baquero Castellanos, & Müller, 2016;Uygun & Gürel, 2017). Priming studies of inflection, on the other hand, have led to more variable outcomes.…”
Section: Mechanisms Of Morphological Decompositionmentioning
confidence: 98%
“…Masked priming studies, for example, revealed efficient priming effects for both the head and the modifier components of compounds, and for both transparent and opaque compounds Duñabeitia, Laka, Perea, & Carreiras, 2009;Fiorentino & Fund-Reznicek, 2009). Furthermore, studies comparing L1 and proficient L2 speakers found similar effects of decomposition of compounds for both speaker groups (González Alonso, Baquero Castellanos, & Müller, 2016;Uygun & Gürel, 2017). Priming studies of inflection, on the other hand, have led to more variable outcomes.…”
Section: Mechanisms Of Morphological Decompositionmentioning
confidence: 98%
“…This perspective on the development of linguistic proficiency among the non-native speakers is consistent with our view in this paper as well. The study on synthetic compounds by González Alonso et al (2016) also provides robust evidence of morphological priming among both native and non-native participants. While their native and non-native speakers differed in terms of RT and accuracy, they patterned similarly to different types of priming and showed almost identical use of morphological structure.…”
Section: Differences In Processing Between Native and Non-native Speamentioning
confidence: 87%
“…The issue of processing by native and non-native speakers has attracted a lot of attention in recent years (inter alia, Conklin & Schmitt 2008;Feldman et al 2010;Clahsen & Neubauer 2010;Diependaele et al 2011;Siyanova-Chanturia et al 2011;De Cat et al 2014;González Alonso et al 2016), but the results do not seem to be unidirectional. 10 Siyanova-Chanturia et al (2011) found that native and non-native speakers differ in terms of speed of processing idioms and novel phrases.…”
Section: Differences In Processing Between Native and Non-native Speamentioning
confidence: 99%
“…The intermediate group was the slowest as in González Alonso et al (2016aAlonso et al ( , 2016b and Li et al (2017). Native speakers recognized compounds significantly faster than noncompounds, and both constituents were activated in compound processing.…”
Section: Discussionmentioning
confidence: 98%
“…This was taken as evidence for decomposition in L2 learners. In another study, González Alonso et al (2016b) compared the processing of English noun-verb-er compounds (e.g. cheerleader) by native and (L1 Spanish) non-native speakers of English via a masked priming task including five conditions: first constituent (e.g., fund-FUNDRAISER), second constituent (e.g.…”
Section: Dead-deadline; Line-deadline) Only Orthographically Overlapmentioning
confidence: 99%